Pemanfaatan Biochar dan Pupuk Kandang Ayam pada Pertanaman Jagung Hibrida di Tanah Ultisol - Samsul Bahri; M Merismon; S Sutejo (Fapetrik-UMPAR, 2020)
This study aims to evaluate the growth and production of hybrid maize on ultisol soils using biochar and chicken manure to support sustainable agriculture. This study used a factorial design based on the randomized block design, which consisted of two treatment factors and three replications. The first factor is the dosage of biochar consisting of 4 levels, namely without biochar (control), 0.25 kg.m-2; 0.5 kg.m-2; and 1 kg.m-2. The second factor is the dose of chicken manure, consisting of four levels, namely without chicken manure (control), chicken manure with a dose of 0.25 kg.m-2; 0.5 kg.m-2; and 1 kg.m-2. The results showed that biochar treatment had a significant effect on plant height. The interaction between treatments has a significant effect on the weight of the ear without the cob. The best biochar treatment was at a dose of 0.25 kg.m-2 while the best treatment of chicken manure was at a dose of 1 kg.m-2.